2003
DOI: 10.1034/j.1600-0714.2003.00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase of mast cells and tumor angiogenesis in oral squamous cell carcinoma

Abstract: These findings suggest that MCs may upregulate tumor angiogenesis in oral SCC, perhaps via MC tryptase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
100
5
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(128 citation statements)
references
References 24 publications
14
100
5
4
Order By: Relevance
“…21,22 Tumours can grow to a size that exceeds its blood supply, leading to tumour necrosis and ulceration. 23 In the present study the patients most frequently presented with an ulcerating lesion. This result is comparable to another study recently conducted in Pakistan wherein the most common clinical presentation of OSCC was as nonhealing indurated ulcer (51.4%) which was significantly common on the buccal mucosa (p=0.001).…”
Section: Discussionmentioning
confidence: 82%
“…21,22 Tumours can grow to a size that exceeds its blood supply, leading to tumour necrosis and ulceration. 23 In the present study the patients most frequently presented with an ulcerating lesion. This result is comparable to another study recently conducted in Pakistan wherein the most common clinical presentation of OSCC was as nonhealing indurated ulcer (51.4%) which was significantly common on the buccal mucosa (p=0.001).…”
Section: Discussionmentioning
confidence: 82%
“…8 -11 Mast cells produce a broad repertoire of cytokines to regulate inflammatory responses, growth factors to stimulate blood vessels and fibroblasts, and enzymes capable of releasing growth factors from extracellular matrix. 5,8 -11,27,28,42 In other human tumors studies it has been shown that mast cell function is complicated with both pro -and antitumor effects, 35,[43][44][45][46] but to the best of our knowledge no studies have previously described differential roles of mast cells depending on the local microenvironment within the same clinical material. It is well established that inflammatory cell types within or surrounding tumors such as tumor-associated macrophages 47 and more lately also neutrophils 48 can be educated by growth factors and cytokines within the tumor microenvironment to acquire pro-or antitumor properties.…”
Section: Discussionmentioning
confidence: 94%
“…[5][6]33,[35][36] FGF-2 has previously been identified as a growth factor released by mast cells by degranulation. 36 FGF-2 is known to be produced in the prostate stroma and acts together with its receptor FGF-R1 as stimulators of epithelial as well as vascular growth and are of major importance in PC in both animal models and patients.…”
Section: Discussionmentioning
confidence: 99%
“…The density of the mast cells in a tissue was studied by using histochemical stains like toluidine blue and [5] alcian blue [2] and immunohistochemically [20] by using mast cell tryptase, heparin, chymase, and carboxypeptidase A. The present study employed the quantification of the mast cells in the area of the 'hot spots'.…”
Section: Discussionmentioning
confidence: 99%